ANALISIS PENGARUH PERTUMBUHAN EKONOMI, INFLASI, NILAI TUKAR, INDEK DJIA, DAN HARGA MINYAK DUNIA TERHADAP INDEK HARGA SAHAM GABUNGAN - Michael Untono (Ma Chung Press, 2015)
This research aims to analyze the consumers ethnocentrism in Malang City affect on the purchase intentions domestic fruits. This study is quantitative causal by using sampling method with 200 respondents. The data collection in this research used field research technique using questionnaires. By using three box method and simple linear regression as the analysis tools, the findings show that the ethnocentrism level of the consumers in Malang City was in high category and the ethnocentrism of the consumers in Malang City positively and significantly affected the purchase intentions towards domestic fruits. This show that high level of ethnocentrism tended to be more attracted to buy domestic fruits and closed themselves from imported fruits. Author suggest to the further research to examines the purchase decision behavior of local fruit.